Why strengthening gap junctions may hinder action potential propagation - Munro Krull, Erin; Börgers, Christoph (Frontiers in Applied Mathematics and Statistics, 2024)
Gap junctions are channels in cell membranes allowing ions to pass directly between cells. They are found throughout the body, including heart myocytes, neurons, and astrocytes. In cardiac tissue and throughout the nervous system, an action potential (AP) in one cell can trigger APs in neighboring cells connected by gap junctions. It is known experimentally that there is an ideal gap junction conductance for AP propagation --- lower or higher conductance can lead to propagation failure. We explain this phenomenon geometrically in branching networks by analyzing an idealized model that focuses exclusively on gap junction and AP-generating currents. As expected, the gap junction conductance must be high enough for AP propagation to occur. However, if the gap junction conductance is too high, then it dominates the cell's intrinsic firing conductance and disrupts AP generation. We also identify conditions for semi-active propagation, where cells in the network are not individually excitable but still propagate action potentials.